2002
DOI: 10.1083/jcb.200202050
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids undergo hop diffusion in compartmentalized cell membrane

Abstract: The diffusion rate of lipids in the cell membrane is reduced by a factor of 5–100 from that in artificial bilayers. This slowing mechanism has puzzled cell biologists for the last 25 yr. Here we address this issue by studying the movement of unsaturated phospholipids in rat kidney fibroblasts at the single molecule level at the temporal resolution of 25 μs. The cell membrane was found to be compartmentalized: phospholipids are confined within 230-nm-diameter (φ) compartments for 11 ms on average before hopping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

89
1,038
8
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 877 publications
(1,137 citation statements)
references
References 40 publications
89
1,038
8
2
Order By: Relevance
“…Although our effective diffusion coefficients were somewhat larger, we attribute this to differences in experimental setup, diffusion models, and fitting routines, since our reported D values for di-8-ANEPPS diffusion in HEKs and OHCs were similar. All values are within the range typically reported for macroscopic effective diffusion coefficients in cell membranes, on the order of 10 −8 to 10 −9 cm 2 /s (Edidin 1987;Fujiwara et al 2002). However, comparisons of quantitative mobility parameters showed distinct differences in lateral mobility between OHC regions.…”
Section: Discussionsupporting
confidence: 81%
“…Although our effective diffusion coefficients were somewhat larger, we attribute this to differences in experimental setup, diffusion models, and fitting routines, since our reported D values for di-8-ANEPPS diffusion in HEKs and OHCs were similar. All values are within the range typically reported for macroscopic effective diffusion coefficients in cell membranes, on the order of 10 −8 to 10 −9 cm 2 /s (Edidin 1987;Fujiwara et al 2002). However, comparisons of quantitative mobility parameters showed distinct differences in lateral mobility between OHC regions.…”
Section: Discussionsupporting
confidence: 81%
“…This is thought to occur due to the steric hindrance imposed by the cytoskeleton on the cytoplasmic domains of these proteins. Treatment of cells with agents that disrupt the cytoskeleton [38], truncation of the cytoplasmic domains of transmembrane proteins [39], or a lack of interaction of membrane proteins with cytoplasmic effector molecules [40] tends to increase their mobility on the cell surface. Likewise, the presence of the bulky heterotrimeric G-protein complex associated with the receptor (since Gproteins, when bound to membrane receptors, could be considered as equivalent to cytoplasmic domains of membrane proteins) could further reduce (over the differences arising due to molecular mass of G-proteins) receptor diffusion, which would be partially relieved when the Gprotein dissociates from the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…• Kusumi and colleagues have shown that the plasma membrane is compartmentalized by a picket fence of transmembrane proteins that are anchored to the submembrane actin cytoskeleton 26,[67][68][69] . The fence allows relative free lateral diffusion of lipids within compartments but restricts movement between compartments.…”
Section: Box 3 Extrapolating From Model Membranes To the Plasma Membranementioning
confidence: 99%